الأسر العلمية في بلاد الشام خلال العصر - -كعبوش إبتسام; د. ح وة فطيمة (جامعة عمار ثليجي الاغواط, 2023)
بً إجػراء في ىػذه الدراسػة الأسػر العلميػة في بػلاد الشػا خػلاؿ العصػر الأيػوبي، في كػل مػن دمشق كحلب كالقدس حيػث تناكلػت الأكضػاع السياسػية كالعلميػة الػتي عرفتهػا بػلاد الشػا خػلاؿ فػتًة الدكلػة الايوبيػة كمػا عرفػت اىتمػا السػلاطتُ بالعلػم كالعلمػاء في تٚيػع التخصصػات كػالأدب كالطػب كالتاريخ كغتَىا كذلك تناكلػة ىػذا الدراسػة مفهػو الأسػر العلميػة كالتعػرؼ علػى أبػرز الأسػر العلميػة في بلاد الشا مع ذكر أىم أعيانها كأبنائهم كأحفادىم الذين إىتموا بالعلو ات١ختلفة. كاف لأفراد تلك الأسر تأثتَ ك اضح في اتٟياة العلمية من خلاؿ التدريس كاىم مؤلفػات، ك أمػا سياسػيا فقػد بً تػولي ات١ناصػب الإداريػة في الدكلػة كػالوزارة ك القضػاء ك السػفارة ك بات١سػتويات ات١ختلفػة ،ككػاف ذلػك طػوؿ الامتػداد الزمػالٍ للدكلػة الأيػوبي بالإضػافة إلى مشػاركة العديػد مػنهم في اتٟركب ضد الغػزك الفرت٧ػي كػذلك حػث ات١سػلمتُ علػى اتٞهػاد ك أمػا اجتماعيػا ك دينيػان فكانػت تلػك الأسػر منخرطػة في المجتمػع بشػكل كاضػح اشػتهر عػدد مػنهم بتقػدلَ ات٠ػدمات الاجتماعيػة لفئػة الفقراء ك الأرامل ك كػاف ت٢ػا تأثػتَ ديػتٍ علػي المجتمػع كمػا عمػل أفرادىػا في الإدارة علػى ات١سػاجد ك الإفتػاء ك ات٠طابػة ك أمػا اتٟيػاة الاقتصػادية فقػد كانػت ت٢ػا مكانػة ك مسػتول مرمػوؽ ك لقد اشتغل افردىا في مهن ت٥تلفة كالتجارة ك النساخة ك غتَىا. الكلمات الدفتاحية: الأسر العلمية، بلاد الشا، العصر الأيوبي. Study Summary: In this study, scientific families in the Levant during the Ayyubid period were conducted in Damascus, Aleppo and Jerusalem, where it dealt with the political and scientific conditions that the Levant knew during the period of the ملخص الدراسة 123 Ayyubid state, as well as the interest of the sultans in science and scientists in all disciplines such as literature, medicine, history and others, as well as this study showed the concept of scientific families and to identify the most prominent scientific families in the Levant with the mention of the most important notables and their sons and Their descendants who were interested in various sciences. The members of these families had an impact and clear in scientific life through teaching and the most important books, and either politically has been assuming administrative positions in the state such as the ministry, the judiciary and the embassy and at different levels, and that was the length of the time extension of the Ayyubid state in addition to the participation of many of them in the wars against the Frankish invasion as well as urging Muslims to jihad and either socially and religiously these families were involved in society clearly a number of them were famous for providing social services to ملخص الدراسة 124 the category The poor and widows and had a religious impact on society as its members worked in the administration of mosques, fatwas and rhetoric, and the economic life has had